Macroeconomic Energy Efficiency Portfolio Model of Indonesia - Fathul Nugroho; Noor Syaifudin (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2017)
There has been a decreasing trend in Indonesia’s energy efficiency. Indonesia’s energy efficiency decreased at the annual rate of 1.4 % over the last 27 years from 246.23 per million Btus in 1980 to 165.51 per million Btus in 2007. In the absence of initiatives by the government as well as the citizens to improve energy efficiency, Indonesia’s energy efficiency will decline gradually in the next 25 years by around 45.51 %. This study attempts to address this policy problem by providing policy recommendations based on in-depth analysis and evaluation of the policy alternatives.